Preparation method of rare metal-doped IZO target material

By doping rare metal oxides into IZO materials, the conductivity and stability of IZO targets are improved, and the lack of performance of pure IZO materials in high temperature environments is solved, and high-performance target preparation is achieved suitable for high temperature environments and a variety of electronic equipment.

CN119822790APending Publication Date: 2025-04-15ZHUZHOU TORCH ANTAI NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510158636.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The conductivity and stability of pure IZO materials still have room for improvement in applications, especially in high temperature environments.

Method used

IZO targets are prepared by mixing indium oxide and zinc oxide in a specific proportion and adding 1% to 5% rare metal oxides (such as tantalum oxide, niobium oxide and palladium oxide), and ball milling, drying, cold isostatic pressure, sintering and annealing.

Benefits of technology

Doping rare metal oxides improves the electronic structure of IZO targets, improves its electrical conductivity and optical properties, enhances the stability and high temperature resistance of the material. It is suitable for applications in high-temperature environments, and has good film forming performance. It is suitable for transparent conductive films, solar cells and touch displays and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a rare metal-doped IZO target material, and relates to the technical field of target material preparation, and the preparation method comprises the following steps: mixing an indium oxide and a zinc oxide according to a mass ratio, and adding a rare metal oxide accounting for 1-5% of the total mass of the indium oxide and the zinc oxide; carrying out wet or dry ball milling by using a ball mill to ensure that the powder is uniformly mixed; drying the mixed powder to remove excessive moisture; pressing through a cold isostatic pressing method to form a target material preform; putting the pressed target material pre-body into a high-temperature furnace, sintering in an oxygen atmosphere, controlling the sintering temperature to be 1200-1600 DEG C, and controlling the sintering time to be 4-8 hours; after sintering, the target material is subjected to annealing treatment in a low-oxygen atmosphere; and target material surface treatment. By doping the rare metal oxide, the electronic structure of the IZO target material can be effectively improved, and the conductivity and the optical performance of the IZO target material are improved; the doping of rare metals is beneficial to enhancing the stability and high temperature resistance of the material, and the material is suitable for being applied in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of target material preparation, and in particular to a method for preparing an IZO target material doped with a rare metal. Background Art

[0002] Indium zinc oxide is a material with good transparent conductive properties. Compared with ITO, IZO has lower cost and better thermal stability, so it has a wider application prospect in the fields of displays, touch screens, photovoltaic devices, etc. However, the conductivity and stability of pure IZO still have room for improvement. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing an IZO target doped with a rare metal, and the specific technical solution is as follows:

[0004] A method for preparing an IZO target doped with a rare metal comprises the following steps:

[0005] Step 1: Indium oxide and zinc oxide are mixed in a mass ratio of (17-27):3, and 1%-5% of the total mass of rare metal oxide is added to obtain an indium zinc mixed component after dispersion;

[0006] Step 2: Use a ball mill to perform wet or dry ball milling for 10 to 20 hours to ensure that the powders are evenly mixed;

[0007] Step 3: After ball milling, the mixed powder is dried at 60-100°C to remove excess water;

[0008] Step 4: Pressing the dried mixed powder by cold isostatic pressing to form a target material precursor;

[0009] Step 5: Place the pressed target material preform into a high temperature furnace and sinter it in an oxygen atmosphere. The sintering temperature is controlled at 1200-1600°C and the sintering time is 4-8 hours.

[0010] Step 6: After sintering, the target material is annealed in a low oxygen atmosphere, the annealing temperature is controlled at 500-700°C, and the annealing time is 2-4 hours;

[0011] Step 7: Target surface treatment.

[0012] Preferably, the rare metal oxide in step 1 is at least one of tantalum oxide, niobium oxide and palladium oxide.

[0013] Preferably, the ball milling media in the ball milling process in step 2 are alumina balls or zirconia balls.

[0014] Preferably, the pressing pressure in step 4 is 10 to 30 MPa.

[0015] Preferably, the pressing method in step 4 is a multi-stage pressure pressing method, and the multi-stage pressure pressing method specifically includes:

[0016] Use a pressing pressure of 10-15 MPa for pre-pressing for 1-2 minutes;

[0017] Use a pressing pressure of 15-20 MPa for medium pressing for 2-4 minutes;

[0018] Use a pressing pressure of 20 to 30 MPa for final pressing for 5 to 10 minutes.

[0019] Preferably, the surface treatment in step 7 comprises laser treatment.

[0020] Preferably, the surface treatment in step 7 includes surface coating treatment, the coating is a transparent conductive film, and the thickness of the transparent conductive film is 50-100 nm.

[0021] Preferably, step 7 specifically includes:

[0022] Using at least one of cerium dioxide, lanthanum trioxide and yttrium trioxide as a rare metal oxide dopant, and preparing a sputtering substrate according to steps 1 to 6;

[0023] The transparent conductive film is formed by sputtering and depositing the sputtering substrate on the surface of the target material through magnetron sputtering.

[0024] Preferably, the indium zinc mixed component in step 1 is doped with aluminum oxide-silicon nitride composite particles.

[0025] Preferably, the aluminum oxide-silicon nitride composite particles are prepared by the following steps:

[0026] Aluminum oxide and silicon nitride are added into a solvent in a mass ratio of (1-3):1 and mixed evenly to obtain a composite component liquid;

[0027] Adding polyvinyl pyrrolidone to the composite component liquid and stirring evenly to obtain a mixed sol;

[0028] The mixed sol is slowly dried at 30-50° C. to obtain an aluminum oxide-silicon nitride composite gel;

[0029] The alumina-silicon nitride composite gel is heated to 800-1000°C in an ammonia atmosphere, and then slowly cooled in a nitrogen atmosphere;

[0030] After cooling, the product is ball-milled for 5 to 10 hours and sieved to obtain aluminum oxide-silicon nitride composite particles of 50 to 100 nm.

[0031] The IZO target material prepared by the method for preparing the rare metal-doped IZO target material provided by the present invention has the following beneficial effects:

[0032] 1. By doping with rare metal oxides, the electronic structure of IZO targets can be effectively improved, and their electrical conductivity and optical properties can be improved; doping with rare metals helps to enhance the stability and high temperature resistance of the material, making it suitable for applications in high temperature environments.

[0033] 2. The prepared IZO target material has good film-forming properties and is suitable for various thin film deposition processes, so it can be effectively used in transparent conductive films, solar cells, touch displays and other fields. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.

[0035] This embodiment provides a method for preparing an IZO target doped with a rare metal, comprising the following steps:

[0036] Step 1: Indium oxide and zinc oxide are mixed in a mass ratio of (17-27):3, and 1%-5% of the total mass of rare metal oxide is added to obtain an indium zinc mixed component after dispersion.

[0037] Step 2: Use a ball mill for wet or dry ball milling for 10 to 20 hours to ensure that the powders are evenly mixed.

[0038] Step 3: After ball milling, the mixed powder is dried at 60-100°C to remove excess moisture.

[0039] Step 4: The dried mixed powder is pressed by cold isostatic pressing to form a target material precursor.

[0040] Step 5: Place the pressed target material preform into a high temperature furnace and sinter it in an oxygen atmosphere. The sintering temperature is controlled at 1200-1600° C. and the sintering time is 4-8 hours.

[0041] Step 6: After sintering, the target material is annealed in a low oxygen atmosphere, the annealing temperature is controlled at 500-700°C, and the annealing time is 2-4 hours.

[0042] Step 7: Target surface treatment.

[0043] The IZO target prepared by the method for preparing the rare metal-doped IZO target provided in this embodiment has the following beneficial effects:

[0044] 1. By doping with rare metal oxides, the electronic structure of IZO targets can be effectively improved, and their electrical conductivity and optical properties can be improved; doping with rare metals helps to enhance the stability and high temperature resistance of the material, making it suitable for applications in high temperature environments.

[0045] 2. The prepared IZO target material has good film-forming properties and is suitable for various thin film deposition processes, so it can be effectively used in transparent conductive films, solar cells, touch displays and other fields.

[0046] Furthermore, in step 1, the rare metal oxide is at least one of tantalum oxide, niobium oxide and palladium oxide.

[0047] Among them, tantalum oxide, as a high-melting-point and stable material, can form a high-conductivity carrier channel in the IZO target and improve the conductivity of the target; niobium oxide also has good conductivity, especially under high temperature conditions, it can help the IZO material maintain a high carrier concentration and improve the conductivity of the material; palladium oxide has high catalytic activity, can increase the conductivity of the IZO target, and can enhance the conductivity by improving the surface electronic structure of the material; and the oxides of tantalum, niobium and palladium have strong thermal stability, which can effectively improve the high-temperature stability of the doped IZO target; tantalum, niobium and palladium oxides also have strong antioxidant ability, which can effectively prevent the IZO material from being oxidized or forming an unstable oxide layer during high-temperature sintering and annealing.

[0048] Furthermore, in step 2, the ball milling medium used in the ball milling process is alumina balls or zirconia balls.

[0049] Furthermore, in step 4, the pressing pressure is 10 to 30 MPa.

[0050] Furthermore, the pressing method in step 4 is a multi-stage pressure pressing method, and the multi-stage pressure pressing method specifically includes:

[0051] Use a pressing pressure of 10 to 15 MPa for pre-pressing for 1 to 2 minutes.

[0052] Use a pressing pressure of 15 to 20 MPa for medium pressing for 2 to 4 minutes.

[0053] Use a pressing pressure of 20 to 30 MPa for final pressing for 5 to 10 minutes.

[0054] Furthermore, the surface treatment in step 7 includes laser treatment.

[0055] Furthermore, the surface treatment in step 7 includes surface coating treatment, the coating is a transparent conductive film, and the thickness of the transparent conductive film is 50-100 nm.

[0056] Among them, the coating of transparent conductive film can improve the electrical conductivity of the material by increasing the carrier concentration, ensuring that the target material has high conductivity in practical applications, and can effectively improve the flatness of the IZO target surface and reduce surface defects, thereby reducing local current density changes caused by surface unevenness, ensuring that the film has consistent deposition quality during the sputtering process and improving photoelectric performance.

[0057] Furthermore, step 7 specifically includes:

[0058] At least one of cerium dioxide, lanthanum trioxide and yttrium trioxide is used as a rare metal oxide dopant, and a sputtering substrate is prepared according to steps 1 to 6.

[0059] The sputtering substrate is sputtered and deposited on the surface of the target material by magnetron sputtering to form a transparent conductive film.

[0060] Among them, cerium dioxide, lanthanum trioxide and yttrium trioxide can improve the surface flatness of the film, reduce light reflection, increase light transmittance, and enhance the stability of the transparent conductive film in high temperature and oxidative environments.

[0061] Furthermore, the indium zinc mixed component in step 1 is doped with aluminum oxide-silicon nitride composite particles.

[0062] Among them, aluminum oxide and silicon nitride are compounded and added to the indium zinc mixed component, which can significantly improve the thermal stability of the target material, protect the indium zinc oxide from oxidation in a high-temperature oxygen atmosphere, and at the same time improve the density of the target material and reduce the generation of pores and cracks. During the sintering process, it can promote the uniform growth of grains, making the target material more dense and uniform after high-temperature sintering and annealing.

[0063] Furthermore, the aluminum oxide-silicon nitride composite particles are prepared by the following steps:

[0064] Aluminum oxide and silicon nitride are added into a solvent in a mass ratio of (1-3):1 and mixed evenly to obtain a composite component liquid.

[0065] Add polyvinyl pyrrolidone into the composite component liquid, stir evenly, and obtain a mixed sol.

[0066] The mixed sol is slowly dried at 30-50° C. to obtain an aluminum oxide-silicon nitride composite gel.

[0067] The alumina-silicon nitride composite gel is heated to 800-1000° C. in an ammonia atmosphere, and then slowly cooled in a nitrogen atmosphere.

[0068] After cooling, the product is ball-milled for 5 to 10 hours and sieved to obtain aluminum oxide-silicon nitride composite particles of 50 to 100 nm.

[0069] Specific examples are provided below. The provided examples may enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0070] Example 1: Tantalum oxide-doped IZO target

[0071] Mix 100g of indium oxide with 15g of zinc oxide, and then add 4.5g of tantalum oxide to ensure uniform mixing. Put the mixed powder into a ball mill for wet ball milling, and the ball milling time is set to 15 hours. Deionized water is used during the ball milling process, and alumina balls are added to enhance the crushing effect. The wet powder after ball milling is transferred to a 60°C oven for drying until the powder is completely free of moisture. The dried powder is evenly filled into the mold and pressed by cold isostatic pressing with an applied pressure of 20MPa to obtain a circular target preform. The target preform is sent to a high-temperature furnace and sintered in an oxygen atmosphere. The sintering temperature is set to 1350°C and the sintering time is 6 hours. During the sintering process, the oxygen flow in the furnace is kept stable to ensure a consistent oxygen atmosphere. After sintering, the target is annealed in a low oxygen atmosphere, the annealing temperature is set to 600°C, and the annealing time is 3 hours. After annealing, an IZO target doped with tantalum oxide is obtained.

[0072] Example 2: IZO target doped with niobium oxide

[0073] 100g of indium oxide was mixed with 15g of zinc oxide, and 3g of niobium oxide was added. After ensuring uniform mixing, the powder was sent to a ball mill for wet ball milling, and the ball milling time was set to 18 hours. During the ball milling process, deionized water was added and alumina balls were used to enhance the crushing effect. The wet powder after ball milling was transferred to an oven at 90°C for drying, and the drying process lasted for 5 hours to ensure that the moisture was completely removed. The dried powder was evenly filled into the mold and pressed by cold isostatic pressing at a pressure of 25MPa to obtain a circular target preform. The target preform was sent to a high-temperature furnace and sintered in an oxygen atmosphere at a sintering temperature of 1300°C for 5 hours, and the oxygen flow was controlled to remain stable. The sintered target was annealed in a low oxygen atmosphere at a temperature of 650°C for 3 hours. After annealing, an IZO target doped with niobium oxide was obtained.

[0074] Example 3: IZO target doped with palladium oxide

[0075] 100g of indium oxide was mixed with 15g of zinc oxide, and 4g of palladium oxide was added. After ensuring uniform mixing, the mixed powder was sent to a ball mill for wet ball milling for 12 hours. During the ball milling process, deionized water was added and crushed using alumina balls. The wet powder after ball milling was transferred to an oven at 70°C for drying for 3 hours. The dried powder was evenly filled into the mold and pressed by cold isostatic pressing at a pressure of 30MPa to form a target preform. The target preform was sent to a high-temperature furnace and sintered in an oxygen atmosphere at a sintering temperature of 1350°C for 7 hours. During the sintering process, ensure that the oxygen flow rate is stable and keep the oxygen atmosphere consistent. The sintered target was annealed in a low oxygen atmosphere at a temperature of 550°C for 2 hours. After annealing, an IZO target doped with palladium oxide was obtained.

[0076] Example 4: IZO target doped with tantalum oxide and niobium oxide

[0077] Mix 100g of indium oxide with 15g of zinc oxide, add 1g of tantalum oxide and 2g of niobium oxide, and ensure uniform mixing. The mixed powder is sent to a ball mill for wet ball milling. The ball milling time is set to 16 hours. Deionized water is used during the ball milling process and alumina balls are added for crushing. The wet powder after ball milling is transferred to an oven at 85°C for drying for 4 hours. The dried powder is evenly filled into the mold and pressed by cold isostatic pressing at a pressure of 28MPa to obtain a target material preform. The target material preform is sent to a high-temperature furnace and sintered in an oxygen atmosphere at a sintering temperature of 1450°C for 6 hours. During the sintering process, the oxygen flow in the furnace is controlled to remain stable. The sintered target is annealed in a low oxygen atmosphere at a temperature of 600°C for 3 hours to finally obtain an IZO target doped with tantalum oxide and niobium oxide.

[0078] Example 5: IZO target doped with tantalum oxide and palladium oxide

[0079] 100g of indium oxide was mixed with 15g of zinc oxide, and 3g of tantalum oxide and 2g of palladium oxide were added to ensure uniform mixing. The mixed powder was sent to a ball mill for wet ball milling for 14 hours. During the ball milling process, deionized water was added and crushed using alumina balls. The wet powder after ball milling was transferred to an oven at 75°C for drying for 4 hours to ensure that the moisture was completely removed. The dried powder was evenly filled into the mold and pressed by cold isostatic pressing with an applied pressure of 25MPa to obtain a target preform. The target preform was sent to a high-temperature furnace and sintered in an oxygen atmosphere. The sintering temperature was set to 1400°C and the sintering time was 5 hours. During the sintering process, the oxygen flow rate was controlled to remain stable to ensure a consistent oxygen atmosphere. The sintered target was annealed in a low oxygen atmosphere at a temperature of 550°C for 3 hours to finally obtain an IZO target doped with tantalum oxide and palladium oxide.

[0080] Example 6: IZO target doped with niobium oxide and palladium oxide

[0081] 100g of indium oxide was mixed with 15g of zinc oxide, and 3g of niobium oxide and 1.5g of palladium oxide were added. After ensuring uniform mixing, the mixed powder was sent to a ball mill for wet ball milling. The ball milling time was 17 hours. Deionized water was used during the ball milling process and alumina balls were added for crushing. The wet powder after ball milling was transferred to an oven at 80°C for drying for 5 hours. The dried powder was evenly filled into the mold and pressed by cold isostatic pressing with an applied pressure of 28MPa to obtain a target preform. The target preform was sent to a high-temperature furnace and sintered in an oxygen atmosphere at a sintering temperature of 1375°C for 5 hours. During the sintering process, ensure that the oxygen flow in the furnace is stable. The sintered target was annealed in a low oxygen atmosphere at a temperature of 625°C for 3 hours, and finally an IZO target doped with niobium oxide and palladium oxide was obtained.

[0082] Example 7: Using Ceria as a Rare Metal Oxide Dopant for Target Surface Modification

[0083] Mix 100g of indium oxide and 15g of zinc oxide, add 12g of cerium dioxide, continue to mix evenly, add the mixed powder to a ball mill, use wet ball milling to mix, the ball milling time is 15h, use deionized water during the ball milling process, and add alumina balls for crushing. The wet powder after ball milling is placed in an oven at 60°C for drying to ensure that the powder is completely dry. The dried mixed powder is evenly filled into the mold and pressed by cold isostatic pressing at a pressure of 20MPa to obtain a target material preform. The target material preform is placed in a high-temperature furnace, the oxygen atmosphere is controlled, the sintering temperature is set at 1350°C, and the sintering time is 6h. During the sintering process, the flow rate of oxygen in the furnace is controlled to ensure that the oxygen atmosphere is stable. The sintered target is annealed in a low oxygen atmosphere, the annealing temperature is set at 600°C, and the annealing time is 3h. After the annealing, the sputtering substrate is obtained.

[0084] The prepared substrate was sputtered and deposited on the target surface by magnetron sputtering to form a transparent conductive film. The parameters of sputtering deposition were set as follows: power 200W, atmosphere of oxygen and argon mixed gas (oxygen accounted for 5%), deposition time 2h, and deposition temperature controlled at 150°C.

[0085] Example 8: IZO target material doped with aluminum oxide-silicon nitride composite particles

[0086] Alumina and silicon nitride were weighed separately, with the mass of alumina being 20g and the mass of silicon nitride being 10g. The two powders were added to 500 ml of ethanol and stirred evenly on a magnetic stirrer until a stable composite component liquid was formed. Polyvinyl pyrrolidone was added to the composite component liquid in an amount of 5% of the mass of the composite component liquid. Stirring was continued in the stirrer to ensure that the polyvinyl pyrrolidone was completely dissolved and evenly distributed to obtain a uniform mixed sol. The mixed sol was placed in an oven and slowly dried at a temperature of 50°C for about 12 hours until the mixed sol was completely dried to obtain an alumina-silicon nitride composite gel. The dried composite gel was placed in an electric furnace and heated to 900°C in an ammonia atmosphere, and the temperature was maintained for 2 hours to promote the nitridation reaction. Subsequently, the atmosphere in the furnace was converted to nitrogen and slowly cooled to room temperature in a nitrogen atmosphere. During the cooling process, the temperature drop rate was controlled within 10°C / h to avoid excessive growth or cracking of the crystals. After cooling, the obtained composite material was taken out and ball milled for 5 hours using a ball mill to ensure that the particles were refined and evenly dispersed. After the ball milling was completed, the composite material was sieved through a sieve to obtain aluminum oxide-silicon nitride composite particles with an average particle size of 60 nm.

[0087] 100g of indium oxide was mixed with 15g of zinc oxide, and then 3g of the above-mentioned alumina-silicon nitride composite particles were added to ensure uniform mixing. The mixed powder was placed in a ball mill for wet ball milling, and the ball milling time was set to 15 hours. Deionized water was used during the ball milling process, and alumina balls were added to enhance the crushing effect. The wet powder after ball milling was transferred to an oven at 60°C for drying until the powder was completely free of moisture. The dried powder was evenly filled into the mold and pressed by cold isostatic pressing with an applied pressure of 20MPa to obtain a circular target preform. The target preform was sent to a high-temperature furnace and sintered in an oxygen atmosphere. The sintering temperature was set to 1350°C and the sintering time was 6 hours. During the sintering process, the oxygen flow in the furnace was kept stable to ensure a consistent oxygen atmosphere. After sintering, the target was annealed in a low oxygen atmosphere, the annealing temperature was set to 600°C, and the annealing time was 3 hours. After the annealing was completed, an IZO target doped with alumina-silicon nitride composite particles was obtained.

[0088] Comparative example: pure IZO target

[0089] Mix 100g of indium oxide with 15g of zinc oxide to ensure uniform mixing. Put the mixed powder into a ball mill for wet ball milling. The ball milling time is set to 15 hours. Deionized water is used during the ball milling process and alumina balls are added. The wet powder after ball milling is transferred to an oven at 60°C for drying until the powder is completely free of moisture. The dried powder is evenly filled into the mold and pressed by cold isostatic pressing with an applied pressure of 20MPa to obtain a circular target preform. The target preform is sent to a high-temperature furnace and sintered in an oxygen atmosphere. The sintering temperature is set to 1350°C and the sintering time is 6 hours. During the sintering process, the oxygen flow in the furnace is kept stable to ensure a consistent oxygen atmosphere. After sintering, the target is annealed in a low oxygen atmosphere. The annealing temperature is set to 600°C and the annealing time is 3 hours. After annealing, a pure IZO target is obtained.

[0090] The IZO targets prepared in Examples 1 to 8 and the comparative example were tested by four-probe method, UV-visible spectrophotometer, electron microscope scanning, linear density method and precision weighing method. The test results are shown in the following table:

[0091] Example Light transmittance (%) Conductivity (S / cm) Surface finish (μm) Sputtering efficiency (%) Example 1 88.5 4.2×10-3 0.3 92.1 Example 2 89.1 4.5×10-3 0.35 90.8 Example 3 87.3 3.8×10-3 0.4 91.2 Example 4 89.8 4.1×10-3 0.32 93.0 Example 5 90.2 4.3×10-3 0.28 92.4 Example 6 88.9 4.0×10-3 0.33 91.7 Example 7 91.5 4.7×10-3 0.30 94.5 Example 8 90.8 4.4×10-3 0.27 93.2 Comparative Example 85.6 3.5×10-3 0.5 80.2

[0092] Through the above tests, it can be verified that the IZO target prepared by the method for preparing the rare metal-doped IZO target provided in this embodiment has excellent properties, including transmittance, electrical conductivity, surface smoothness and sputtering efficiency, and is suitable for the preparation of high-performance transparent conductive films.

[0093] The principles and implementation methods of the present invention are described herein using specific examples, and the description of the above embodiments is only used to help understand the method and core ideas of the present invention. The above are only preferred implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention, which should be within the protection scope of the present invention.

Claims

1. A method for preparing an IZO target doped with a rare metal, characterized in that: The steps include: S1: mixing indium oxide and zinc oxide in a mass ratio of (17-27):3, and adding 1%-5% of the total mass of rare metal oxides to obtain an indium-zinc mixed component after dispersion; S2: Use a ball mill for wet or dry ball milling for 10 to 20 hours to ensure that the powders are evenly mixed; S3: After ball milling, the mixed powder is dried at 60-100°C to remove excess water; S4: Pressing the dried mixed powder by cold isostatic pressing to form a target material precursor; S5: placing the pressed target material preform into a high temperature furnace and sintering it in an oxygen atmosphere, with the sintering temperature controlled at 1200-1600° C. and the sintering time being 4-8 hours; S6: After sintering, the target material is annealed in a low oxygen atmosphere, the annealing temperature is controlled at 500-700° C., and the annealing time is 2-4 hours; S7: target surface treatment.

2. The preparation method according to claim 1, characterized in that: The rare metal oxide in step S1 is at least one of tantalum oxide, niobium oxide and palladium oxide.

3. The preparation method according to claim 1, characterized in that: The ball milling medium in the ball milling process in step S2 is selected from alumina balls or zirconia balls.

4. The preparation method according to claim 1, characterized in that: The pressing pressure in step S4 is 10 to 30 MPa.

5. The preparation method according to claim 4, characterized in that: The pressing method in step S4 is a multi-stage pressure pressing method, and the multi-stage pressure pressing method specifically includes: Use a pressing pressure of 10-15 MPa for pre-pressing for 1-2 minutes; Use a pressing pressure of 15-20 MPa for medium pressing for 2-4 minutes; Use a pressing pressure of 20 to 30 MPa for final pressing for 5 to 10 minutes.

6. The preparation method according to claim 1, characterized in that: The surface treatment in step S7 includes laser treatment.

7. The preparation method according to claim 2, characterized in that: The surface treatment in step S7 includes surface coating treatment, the coating is a transparent conductive film, and the thickness of the transparent conductive film is 50-100 nm.

8. The preparation method according to claim 7, characterized in that: Step S7 specifically includes: Using at least one of cerium dioxide, lanthanum trioxide and yttrium trioxide as a rare metal oxide dopant, and preparing a sputtering substrate according to steps S1 to S6; The transparent conductive film is formed by sputtering and depositing the sputtering substrate on the surface of the target material through magnetron sputtering.

9. The preparation method according to claim 1, characterized in that: The indium zinc mixed component in step S1 is doped with aluminum oxide-silicon nitride composite particles.

10. The preparation method according to claim 9, characterized in that: The aluminum oxide-silicon nitride composite particles are prepared by the following steps: Aluminum oxide and silicon nitride are added into a solvent in a mass ratio of (1-3):1 and mixed evenly to obtain a composite component liquid; Adding polyvinyl pyrrolidone to the composite component liquid and stirring evenly to obtain a mixed sol; The mixed sol is slowly dried at 30-50° C. to obtain an aluminum oxide-silicon nitride composite gel; The alumina-silicon nitride composite gel is heated to 800-1000°C in an ammonia atmosphere, and then slowly cooled in a nitrogen atmosphere; After cooling, the product is ball-milled for 5 to 10 hours and sieved to obtain aluminum oxide-silicon nitride composite particles of 50 to 100 nm.

Citation Information

Cited By

  • IGZO ceramic target material and preparation method thereof

    CN120794574A